2020
DOI: 10.1007/s10926-020-09891-1
|View full text |Cite
|
Sign up to set email alerts
|

Passive Trunk Exoskeleton Acceptability and Effects on Self-efficacy in Employees with Low-Back Pain: A Mixed Method Approach

Abstract: Purpose Determinants of successfully introducing passive exoskeletons in the working environment to decrease mechanical loading on the back, are acceptability of the device to management and employees, including self-efficacy of employees when using the device. Therefore, the aim of this study was to assess self-efficacy of employees with low-back pain when using an exoskeleton and the acceptability of such a device to these employees and their managers. Methods We used a mixed method approach. We quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
0
33
1
1
Order By: Relevance
“…On the other hand, asymptomatic individuals seemed to not be willing to endure this downside, with no apparent benefit. To better elucidate the reasons for these differences, focus groups should be implemented [ 15 , 16 ] in the future. Indeed, it has been previously stressed by focus group participants that they see a potential of the exoskeleton use in rehabilitation, but not prevention [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, asymptomatic individuals seemed to not be willing to endure this downside, with no apparent benefit. To better elucidate the reasons for these differences, focus groups should be implemented [ 15 , 16 ] in the future. Indeed, it has been previously stressed by focus group participants that they see a potential of the exoskeleton use in rehabilitation, but not prevention [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a major issue that remains mostly unresolved, is the subjective perception and acceptance of the device by the users, for which the abovementioned studies have shown mixed and inconclusive results. This issue has been lately addressed with qualitative methods, such as focus groups [ 15 , 16 ]. Although some concerns were expressed, LBP patients acknowledged the potential of the exoskeleton and generally show a willingness to use it [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations